Stability of Equilibria with Externalities - Howitt, Peter; McAfee, R. Preston (Quarterly Journal of Economics, 1988)
It is shown that, in a class of models with multiple externalities (one positive and one negative), all stationary equilibria may be locally stable to perturbations, in the sense that there exist perfect foresight trajectories leading back to the equilibrium. Thus, scale diseconomies (arising, for example, out of a common resource pool) generally overturn the Liviatan-Samuelson result, that equilibria are either saddlepoints or sources.